Influence of Compression Ratio on Flywheel Dimension for a Naturally Aspirated Spark Ignition Engine: A Numerical Study - Aan Yudianto; Peixuan Li (Universitas Muhammadiyah Magelang, 2020)
The proper design of the flywheel undeniably determines in tuning the engine to confirm the better output engine performance. The aim of this study is to mathematically investigate the effect of various values of the compression ratio on some essential parameters to determine the appropriate value for the flywheel dimension. A numerical calculation approach was proposed to eventually determine the dimension of the engine flywheel on a five-cylinder four-stroke Spark Ignition (SI) engine. The various compression ratios of 8.5, 9, 9.5, 10, 10.5, and 11 were selected to perform the calculations. The effects of compression ratio on effective pressure, indicated mean effective pressure (IMEP), dynamic irregularity value of the crankshaft, and the diameter of the flywheel was clearly investigated. The study found that 2.5 increment value of the compression ratio significantly increases the effective pressure of about 41.53% on the starting of the expansion stroke. While at the end of the compression stroke, the rise of effective pressure is about 76.67%, and the changes in dynamic irregularity merely increase by about 1.79%. The same trend applies to the flywheel diameter and width, which increases 2.08% for both.